2019
DOI: 10.1101/696021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing auditory processing endophenotypes associated with Schizophrenia in individuals with 22q11.2 Deletion Syndrome

Abstract: Background: 22q11.2 Deletion Syndrome (22q11.2DS) is the strongest known molecular risk factor for schizophrenia. Brain responses to auditory stimuli have been studied extensively in schizophrenia and described as potential biomarkers of vulnerability to psychosis. We sought to understand whether these responses might aid in differentiating individuals with 22q11.2DS as a function of psychotic symptoms, and ultimately serve as signals of risk for schizophrenia.Methods: A duration oddball paradigm and high-dens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 111 publications
1
10
1
Order By: Relevance
“…An aforementioned meta-analysis showed that there was a trend for decreased MMN amplitude in relatives of patients ( 90 ), which was in agreement with another meta-analysis ( 100 ). A recently published study also demonstrated an intrinsic effect of 22q11.2 deletion syndrome, a molecular risk factor for schizophrenia, on MMN ( 54 ), suggesting a potential genetic link as well. Therefore, while a growing body of studies is supporting MMN as an endophenotype, the findings are mixed.…”
Section: Mismatch Negativitymentioning
confidence: 81%
See 1 more Smart Citation
“…An aforementioned meta-analysis showed that there was a trend for decreased MMN amplitude in relatives of patients ( 90 ), which was in agreement with another meta-analysis ( 100 ). A recently published study also demonstrated an intrinsic effect of 22q11.2 deletion syndrome, a molecular risk factor for schizophrenia, on MMN ( 54 ), suggesting a potential genetic link as well. Therefore, while a growing body of studies is supporting MMN as an endophenotype, the findings are mixed.…”
Section: Mismatch Negativitymentioning
confidence: 81%
“…MMN and P50 are among the neurophysiological markers that are being considered as potential endophenotypes in this disease ( 52 54 ). In addition, as MMN and P50 are markers of neurological processes that are thought to be important for cognitive functioning in patients with schizophrenia, they have also garnered interest as predictive biomarkers to see if an intervention will improve cognition ( 55 60 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mixed nature of the current 22q11.2DS sample (individuals with and without symptoms) could have impacted the ability to detect differences between those with 22q11.2DS and their age-matched neurotypical peers. A recent EEG study focused on basic auditory processing in this population suggested differences between those with and without psychotic symptomatology and argued for the presence of two opposite mechanisms in those with the deletion: one that relates to a process specific to the deletion itself and gives rise to larger amplitudes, and another, associated with psychosis that results, as in schizophrenia, in decreases in amplitude ( Francisco et al, 2020 ). And, indeed, here, whereas the 22q11.2DS− group did not differ from the neurotypical controls, but presented increased amplitudes when compared to the schizophrenia group; 22q11.2DS+ did not differ from the individuals with schizophrenia, but presented decreased amplitudes when compared to the neurotypical controls.…”
Section: Discussionmentioning
confidence: 99%
“…The DiGeorge syndrome, also known as velocardiofacial or 22q11.2 deletion syndrome (22q11.2DS), is the consequence of a hemizygous microdeletion (1.5-3 Mb) on chromosome 22, with an incidence of 1 in 4000 [117]. The syndrome often presents with different neuropsychiatric symptoms [118], including schizophrenia [119]. Additionally, individuals with 22q11.2DS manifest with attention-deficit hyperactive disorder (ADHD), ASD, anxiety, depressive, and bipolar disorders [120,121].…”
Section: Digeorge Syndromementioning
confidence: 99%